2021
DOI: 10.4018/ijsecsr.2021010101
|View full text |Cite
|
Sign up to set email alerts
|

Dimensional Entrepreneurial Deployment of Information and Communication Technology for Economic Empowerment in Nigeria

Abstract: The success of entrepreneurship practice largely depends on the opportunities provided by an environment and the intuition and innovativeness of the enterprising individuals to leverage on the opportunities. The emerging information and communication technologies (ICT) in Nigeria brought about arrays of opportunities for ICT entrepreneurship practice in the country. Conscientious examination of the dimensional exploration of the information-driven technologies for economic activities among the enterprising ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 18 publications
1
1
0
Order By: Relevance
“…Similarly, with a long-term coefficient of (0.004), information and communication technology (MCS) has a strong positive impact on Nigeria's economic growth. The results align with the studies conducted by [47,50,48,13], and others that have demonstrated a noteworthy and affirmative influence of ICT on economic growth. Notably, [13] also employ mobile cellular subscription as a stand-in for ICT.…”
Section: The Role Of Ict In the Tourism-growth Nexussupporting
confidence: 91%
See 1 more Smart Citation
“…Similarly, with a long-term coefficient of (0.004), information and communication technology (MCS) has a strong positive impact on Nigeria's economic growth. The results align with the studies conducted by [47,50,48,13], and others that have demonstrated a noteworthy and affirmative influence of ICT on economic growth. Notably, [13] also employ mobile cellular subscription as a stand-in for ICT.…”
Section: The Role Of Ict In the Tourism-growth Nexussupporting
confidence: 91%
“…The study concludes that whereas internet usage has a negative and negligible link with economic growth in Nigeria, mobile phone membership has a positive and substantial influence on economic growth both in the short and long term. Additionally, [47] look on the dimensional entrepreneurial use of ICT for Nigerian economic empowerment. They highlighted how the nation's growing ICT potential have accelerated online enterprises and the merchandising of ICT resources, creating more job chances in the unorganized sector and enabling workers to meet their fundamental necessities.…”
Section: Ict and Economic Growthmentioning
confidence: 99%